"A dialogue of deliberated uncertainty" : an interpretation of religious pluralism within the context of democracy : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Religious Studies at Massey University - Harper, Dian Merrilyn (Massey University, 2000)
When Race, the editor of World Faiths Encounter, launched the journal in 1992 he indicated that "the mixed contents" were "intended to aid many kinds of dialogue." He spoke of this in terms of an encounter which he perceived as a "many sided endeavour... [that] requires openness, respect and receptivity to whatever comes." 1 Race, Alan, "Launching a Journal". World Faiths Encounter. Number 1, [March, 1992] page 2. The focus of this thesis is to investigate one aspect of that encounter, the nature of religious pluralism within the context of democracy and its resolution within the concept of "process pluralism". In line with this intention, the key statements in several selected articles, those relevant to the topic of "Religion in Democracy and Democracy in Religion." from World Faiths Encounter have been identified and catalogued using an adapted version of Race's familiar delineation of exclusivism, inclusivism and pluralism. These results are recorded in a database [appendix 1] that has been constructed for this purpose. This analysis has been useful to get a preliminary idea of where the writers are in terms of their investment in pluralism but its main function has been to identify questions, arising from the key statements of each, that relate directly to pluralism in the context of democracy. Each of these questions is addressed in a series of reports that make up the main body of the thesis. While each report follows its own separate enquiry, all of the reports also contain within their conclusion a further common question: How do the observations made in this paper contribute to a profile of process pluralism? The various answers to this common question make up the final report of the thesis and address the question of what is meant by the thesis title, "A Dialogue of Deliberated Uncertainty." It is suggested that this report be read first to provide an overview of what is to follow and to "come to grips" at once with what is meant by the concept of "process pluralism" that is introduced and developed in the thesis.
Keywords: Religious pluralism; Religion and politics; Democracy